Nightmare frequency and nightmare distress in poor sleepers: a cross-sectional study - Schredl, Michael (Journal of sleep research, 2025)
Having nightmares can contribute to poor sleep quality, and having sleep problems can be accompanied by increased nightmare frequency. The etiological models of insomnia and nightmare disorder also show some parallels. The present cross-sectional study included 654 participants (509 women, 144 men, 1 non-binary) with mild to moderate sleep problems (mean age: 41.19 ± 12.95 years). As expected, nightmare frequency was elevated compared to previously published findings of a representative sample (large effect size). Moreover, waking-life stress level moderated—at least partially—the relationship between poor sleep quality and nightmare frequency. Like previous studies, gender and waking-life stress contributed significantly to nightmare distress—after controlling for the effect of nightmare frequency on nightmare distress. Overall, the present study emphasises the close link between sleep problems and nightmares. Based on previous studies, it seems very beneficial to offer nightmare sufferers additional modules of cognitive-behavioural therapy for insomnia and similarly offer patients with insomnia disorder who also reported elevated nightmare distress a nightmare treatment module like Imagery Rehearsal Therapy.